POTENTIAL OF FRUIT PRODUCTION TEMBESU (Fagraea fragrans Roxb.) OF OGAN ILIR (OI) AND OGAN KOMERING ILIR (OKI) THE SOUTH OF SUMATERA - Dharmawati F. Djam’an; Kurniawati Purwaka Putri; Evayusvita Rustam; Agus Astho Pramono (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Tembesu (Fagraea fragrans Roxb.) Is one tree that is very popular in Southern Sumatra region as raw material for carving and furniture industry. The need for wood reaches 3 120 m³ per year and has been supplied from plants that grow naturally or from community forest. The purpose of this study was to determine the production potential of fruit each branch so that it can predict preparations to facilitate the expansion of planting seedlings. Tembesu trees including types with wide adaptability to a place to grow as on dry land, waterlogged soil or land tides. This type includes the category of intermediate cycle (10-30) years. The average production of fruit each branch of Ogan Ilir 38 094.53 fruits, 1000 grain weight of 0.3066 gr and initial KA 7.2% textured clay dusty land. Production of Ogan Komering Ilir with sandy soil texture reach 88 862.27 fruits, 1000 grain weight of 0.2548 gr and initial seed KA 7.7%. The average production of fruit each branch is influenced by soil texture is sandy land (OKI, swamp / stagnant) production higher than that of land dusty clay (OI, dry / stagnant).Key words : tembesu, fruit production, wide adaptability